TINDAK PIDANA DAN PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Ana Indriana (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
Banking is one sector that has an important role in various fields, among others, in community activities, especially in the financial field, as well as economic activities to meet one's personal needs. In conducting banking activities especially sharia banking, does not rule out the occurrence of a dispute or dispute in it. This dispute must ultimately be resolved by both parties namely the bank and the customer because both parties have the same position as the parties concerned. In the case of dispute settlement in sharia banking, there are two (2) dispute resolution methods namely dispute settlement through litigation (court lane) and dispute settlement through non litigation (out-court) path where each method of settlement has weaknesses and their respective advantages. The basis for dispute settlement within the sharia banking itself is regulated in Law No. 21 of 2008 concerning Sharia Banking.